In the Company of Gentiles: Exploring the History of Integrated Jews in British Columbia, 1858-1971 - Nordlinger McDonnell, Lillooet (Université d'Ottawa / University of Ottawa, 2011)
By way of five microhistories focusing on the lives of Cecelia Davies Sylvester, Hannah Director, Leon Koerner, Harry Adaskin, and Nathan Nemetz, this study examines various modes of integration for Jews within particular periods of British Columbian (BC) history. Each microhistory explores the boundaries that were crossed and fostered by Jews whose careers and social contributions led them outside the confines of the established Jewish community. These Jews represent the vanguard of Jewish integration for each era to which they contributed.
Keywords: professional Jews; British Columbia Jews; Jewish Jurists; Nathan Nemetz; Leon Koerner; Hannah Director; Harry Adaskin; Cecelia Davies Sylvester; Jewish lumber barons; Integrated Jews